2018
DOI: 10.1038/s41535-018-0095-2
|View full text |Cite
|
Sign up to set email alerts
|

Path to stable quantum spin liquids in spin-orbit coupled correlated materials

Abstract: The spin liquid phase is one of the prominent strongly interacting topological phases of matter whose unambiguous confirmation is yet to be reached despite intensive experimental efforts on numerous candidate materials. Recently, a new family of correlated honeycomb materials, in which strong spin-orbit coupling allows for various bond-dependent spin interactions, have been promising candidates to realize the Kitaev spin liquid. Here we study a model with bond-dependent spin interactions and show numerical evi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 43 publications
4
55
0
Order By: Relevance
“…Although zigzag phases have been detected in Na 2 IrO 3 and α-RuCl 3 , the spin Hamiltonian of both compounds remains uncertain, and it probably involves both other anisotropic interactions and further neighbor isotropic couplings. 25,28,30,32,33,49,50 In particular, the NN off-diagonal exchange Γ may play an important role in both Na 2 IrO 3 and α-RuCl 3 , e.g. in fixing the global directions of the spins in the zigzag state at zero field.…”
Section: Discussionmentioning
confidence: 99%
“…Although zigzag phases have been detected in Na 2 IrO 3 and α-RuCl 3 , the spin Hamiltonian of both compounds remains uncertain, and it probably involves both other anisotropic interactions and further neighbor isotropic couplings. 25,28,30,32,33,49,50 In particular, the NN off-diagonal exchange Γ may play an important role in both Na 2 IrO 3 and α-RuCl 3 , e.g. in fixing the global directions of the spins in the zigzag state at zero field.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pure SA interactions lead to a macroscopically degenerate manifold of classical ground states in hyperhoneycomb (3D) lattices [48], a signature of frustration [29]. Quantum calculations on finite size honeycomb lattices (2D) also confirm absence of magnetic order in pure SA models [48], and it was recently suggested that this ground state continuously connects to the Kitaev QSL in the presence of bond anisotropy [32]. Our single crystal XRD experiments at high pressure show the same type of (X,Y)-and Z-bond anisotropy seen in the theoretical calculations despite the lack of exact agreement in the compressibility of the lattice parameters.…”
mentioning
confidence: 95%
“…Remarkably, ab initio calculations on anisotropically compressed lattices based on J-K-Γ spin hamiltonians (J-Heisenberg, K-Kitaev, Γ-symmetric anisotropic (SA) exchange interactions, respectively) [28] show that SA interactions become dominant at an effective pressure of P ∼ 1.4 GPa. Since pure SA models lead to largely degenerate ground states in classical models [29,30] and quantum spin liquids in quantum models [31,32], the shift in the balance of bond-directional exchange interactions driven by anisotropic compression may explain the emergence of quantum paramagnetism and provides one possible route for realization of a novel QSL state in compressed β-Li 2 IrO 3 .…”
mentioning
confidence: 99%
“…In these candidate materials, as with other QSL candidates, the presence of additional symmetry allowed terms (Heisenberg and bond-dependent off-diagonal interactions in this case), produces long range magnetic order. 10,10,29,37 Despite extensive studies and evidence for fractional particles 11,34,38,39 , the relative size of the non-Kitaev terms and the range over which they are relevant remains controversial 37,40 . In α-RuCl 3 , these non-Kitaev terms lead to a magnetically ordered phase below 7 K, which could be destroyed by an in-plane magnetic field [41][42][43][44][45] .…”
mentioning
confidence: 99%